Improving the Performance of Batik Craft MSMEs in Jambi City Through a Comparative Advantage Strategy Using the House Model Approach - Mulia Inda Purwati; A. Rozi; Efandri Agustian (Dinasti International Journal of Education Management and Social Science, 2025)
As a country that has various types of creative industries such as the batik craft industry. Batik should be able to become one of the business fields that can support the economy (Nengsih et al., 2021). This is also what makes the government serious in managing batik crafts so that they can be used as superior products. The Jambi Batik industry is currently shrinking, one of the reasons is that most of the Jambi patterned batik circulating in the market is supplied from Java. This causes the price of Javanese Jambi batik to be more popular with the public because the price is cheaper. One of the strategies that can be applied to improve the performance of MSMEs is through the Comparative Advantage  approach (Porter, 1985). This strategy emphasizes the use of competitive advantages possessed by MSMEs in order to compete effectively in the market (Suryana A, Kartika R, 2022). To support the implementation of the Comparative Advantage strategy, this study adopts The House Model approach, which is a business development model based on competitive advantage. The House Model consists of several main elements, such as a strong business foundation, innovation strategy, resource management, and the role of stakeholders in supporting business growth (Nengsih et al, 2021 and Schmitz, 2007). The results of this study show that Jambi batik crafts can develop and compete with crafts in other batik centers by utilizing local and innovative materials to improve the quality and added value of Jambi batik, so that the results of these batik products have their own characteristics. Furthermore, from the Marketing side, it must also be based on local identity by not forgetting the use of digitalization to open up access to the global market.